WITHDRAWN: Effect of bonding time and boron carbide percentage on diffusion bonding characteristics for copper/copper matrix composites (Cu + Cu%B4C) - ESKi, Özkan; ELHEMSHERI, Marwan Abdussalam M. (Elsevier BV, 2021)
Abstract In this study, the Joining characteristics of pure copper (Cu) and copper matrix composites reinforced by 2.5, 5.0, 7.5 wt% of Boron Carbide (B4C), were investigated. The diffusion bonding (DB) process was prepared at a temperature of 800 °C, and different holding times of 30, 45, and 60 min. During DB, a uniaxial load of 2 MPa was applied. The dissimilar materials joining quality was studied to determine the influences of diffusion time and B4C particulates on bonding properties. Scanning electron microscopy SEM assays and energy dispersion spectrophotometry EDS element analyzes were performed to determine joint interface properties and to determine mechanical characterization with shear strength SS measurements.
Keywords: 7. Clean energy